Exploratory Study of the Application of Online Learning in Teaching Skills and Microteaching Courses - Septyan Budy Cahya; Yoyok Soesatyo; Siti Sri Wulandari; Dewie Tri Wijayati Wardoyo (International Journal of Studies in International Education, 2024)
The This study aims to explore the implementation of online learning of Teaching Skills and Microteaching courses, focusing on three main aspects: preparation, implementation, and evaluation of learning. This study also considers the challenges that arise due to student involvement in the Merdeka Belajar Kampus Merdeka (MBKM) program, which often affects the consistency of their participation in regular learning. This study was conducted using a qualitative descriptive method with a case study design. The results showed that online learning was quite effective in conveying teaching skills theory through digital materials and asynchronous activities. However, teaching practice simulations faced several limitations, such as the difficulty of observing non-verbal elements, classroom management, and spontaneous responses of students during online simulations. Technical constraints, especially unstable internet connections, were also major obstacles in implementing learning. In addition, students involved in MBKM reported difficulties in dividing time between program assignments and regular course preparation, which impacted their participation and engagement.